Electronic magnification and perceived contrast of video - Haun, Andrew (2012)
Electronic magnification of an image results in a decrease in its perceived contrast. The decrease in perceived contrast could be due to a perceived blur or to limited sampling of the range of contrasts in the original image. We measured the effect on perceived contrast of magnification in two contexts: either a small video was enlarged to fill a larger area, or a portion of a larger video was enlarged to fill the same area as the original. Subjects attenuated the source video contrast to match the perceived contrast of the magnified videos, with the effect increasing with magnification and decreasing with viewing distance. These effects are consistent with expectations based on both the contrast statistics of natural images and the contrast sensitivity of the human visual system. We demonstrate that local regions within videos usually have lower physical contrast than the whole, and that this difference accounts for a minor part of the perceived differences. Instead, visibility of ‘missing content’ (blur) in a video is misinterpreted as a decrease in contrast. We detail how the effects of magnification on perceived contrast can be measured while avoiding confounding factors.